DESAIN SISTEM E-LEARNING KAMPUS BERBASIS WEB DENGAN PENERAPAN HASHING, ENKRIPSI SIMETRIS, DAN TOKEN KEAMANAN - Hendra Finur; Muhammad Furqan Hakim; Riska Riska; Sahril Saputra (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2026)
Information technology adoption in online learning requires higher education institutions to provide an e-learning system that is not only functional but also secure in managing academic and user data. E-learning platforms commonly store sensitive information such as user identities, academic grades, and learning activities, making security a critical factor. However, many e-learning systems are developed without adequate security design from the early stages. This study aims to design a campus e-learning web application using pure PHP by applying cryptography-based data security mechanisms. The research method employs a Research and Development (R&D) approach with a system design orientation. The cryptographic aspects incorporated in the proposed design include cryptographic hashing for securing user authentication, symmetric encryption for protecting sensitive data, and security token mechanisms to ensure the integrity of sessions and system requests. The system design is modeled using Unified Modeling Language (UML) to represent functional requirements and an Entity Relationship Diagram (ERD) to design the database structure. The results of this study are an e-learning system design that includes use case diagrams, a database design, and a cryptography-based security mechanism design. This design is expected to serve as a reference for developing a secure, well-structured campus e-learning application aligned with academic needs.